Slavery to Liberation The African American Experience - Farrington, Joshua; Powell, Norman W.; Graham, Gwendolyn; Anyanwu, Ogechi E. (Open textbook library., 2019)
Slavery to Liberation: The African American Experience gives instructors, students, and general readers a comprehensive and up-to-date account of African Americans’ cultural and political history, economic development, artistic expressiveness, and religious and philosophical worldviews in a critical framework. It offers sound interdisciplinary analysis of selected historical and contemporary issues surrounding the origins and manifestations of White supremacy in the United States. By placing race at the center of the work, the book offers significant lessons for understanding the institutional marginalization of Blacks in contemporary America and their historical resistance and perseverance.